Neuropathic pain after a dental procedure in an older adult with Alzheimer's disease: a case report - Erica Negrini LIA; Marco Polo Dias FREITAS; Lucas Fernando TABATA; Fabiano MALUF; Sergio Bruzadelli MACEDO (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT Neuropathic pain occurs when there is damage to nervous system structures, particularly as a result of direct injury or disease. It can occur in the orofacial territory after dental implants placement. Oral rehabilitation is often performed with dental implant placement for older adults. However, the general health status should be considered, requiring a careful assessment of the patient and the identification of geriatric conditions that could lead to predictable failures. The purpose of this case report is to present the diagnosis and treatment of neuropathic pain after dental implant placement in an older adult with dementia due to Alzheimer's disease.